Research, Networking, and Capacity Building - Mohamedbhai, Goolam (International Higher Education, 2012)
Regional networking and collaboration is increasingly being used to promote research and capacity building in African universities. Some of the current networking initiatives are outlined and the challenges they encounter identified.